Barbus urmianus, a synonym of Barbus cyri (Teleostei: Cyprinidae) - Jouladeh-Roudbar, Arash; Ghanavi, Hamid Reza; Kaya, Cüneyt; Freyhof, Jörg (Zootaxa, 2023)
Barbus urmianus, from the upper Mahabad River in Lake Urmia basin, was distinguished from B. cyri based on several morphological characters. Our analysis demonstrated very small molecular (COI) differences between both species and mostly overlapping or identic morphological character states. Therefore, Barbus urmianus is treated as a junior synonym of B. cyri.